(untitled) (Development Service Industry Management, 2024)
This article describes the opportunities that organized capital markets provide to business structures, as well as the main aspects of managing a company’s investment activities in organized capital markets. This includes the essence, tasks, and strategic approaches to optimizing the investment efficiency of the enterprise. The quality of financial management and its role in managing enterprise activities is becoming increasingly important for many business structures. The number of new risks and challenges that need to be mitigated, along with the growing array of financial instruments available both in Ukraine and globally, necessitates a systematic approach to managing the investment activities of enterprises. Managing enterprise investment activities in organized capital markets is relevant for several reasons. Enterprises operate in highly competitive environments, requiring effective investment management to remain competitive and enhance market positions. Organized capital markets bring together investors from around the world, offering enterprises opportunities to obtain capital for their investment projects and expansion. Investment activities have become more complex due to the emergence of new financial instruments and economic trends, requiring specialized approaches to investment management. Effective investment management allows enterprises to formulate long-term development strategies, promoting innovation and enhancing operational efficiency. Analyzing and developing an effective investment strategy in organized capital markets is crucial for the growth, sustainability, and development of enterprises. Previous researches on enterprise investment management in organized capital markets highlight the importance of effective financial investment management for enhancing the profitability and financial stability of enterprises. Comprehensive strategies are needed also to make strategic financial investments for diversification and long-term growth, despite existing infrastructural, economic, and political challenges. The importance of effective portfolio management of financial investments, particularly in unstable markets, is also emphasized. Financial investments offer significant advantages by utilizing a broad spectrum of investment instruments across the profitability-risk and profitability-liquidity spectrum, making them a flexible and essential aspect of enterprise strategy. In summary, the essence of managing enterprise investment activities in organized capital markets involves defining investment goals and ways to achieve them, evaluating investment objects, managing the investment portfolio, and analyzing investment efficiency. The tasks of such activities are to achieve the defined investment goals using the specific characteristics of the company and advantages of assets traded in organized capital markets.